The modes of provision of prison services in a comparative perspective - Cabral, Sandro (2008)
This paper aims to compare the performance of two modes of provision of prison services: public, and with the participation of private companies. There are few empirical studies concerning the alternative modes of governance in this sector, which differs from other public utilities in that there is an absence of network externalities and scale economies. In addition, an understanding of informal institutions is crucial for the performance of the service provider, either public or private. In this paper, we build a comparative analysis of two case studies of similar correctional facilities, one public and the other outsourced to a private company under the supervision of civil servants (hybrid governance structure), both located in the same region of Brazil. We found that the privately operated facility has achieved better performance indicators (in terms of number of escapes, riots, deaths, assistance to inmates etc.) than the public facility, which in part refutes the arguments of Hart, Shleifer and Vishny (1997) against private participation in prison services. We conclude that the reasons for these differences are related to lower levels of administrative controls; to the presence of civil servants within the privately operated prison, which contributes to reducing information asymmetries; to greater incentives for the private operator: to monitor employees, to bypass local judiciary constraints and to fulfill contractual obligations.